2021
DOI: 10.1007/s00125-021-05526-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal diabetes during pregnancy with high refractive error in offspring: a nationwide population-based cohort study

Abstract: Aims/hypothesis We aimed to investigate the associations between maternal diabetes before or during pregnancy and the risk of high refractive error (RE) in offspring until the age of 25 years. Methods This nationwide register-based cohort study comprised 2,470,580 individuals born in 1977-2016. The exposure was maternal diabetes during or before pregnancy (type 1 diabetes, type 2 diabetes and gestational diabetes). Cox regression was used to examine the association between maternal diabetes and the risk of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
3
13
1
Order By: Relevance
“…3,4 Growing evidence has shown that prenatal adversity, such as maternal gestational diabetes and maternal smoking during pregnancy, is associated with increased risk of overall or type-specific REs in offspring. [5][6][7][8][9][10][11] These findings indicate that adverse prenatal or intrauterine environments might contribute to the development of high RE later in life. 12 Hypertensive disorder of pregnancy (HDP) is one of the most common complications during pregnancy, affecting 5% to 10% of pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Growing evidence has shown that prenatal adversity, such as maternal gestational diabetes and maternal smoking during pregnancy, is associated with increased risk of overall or type-specific REs in offspring. [5][6][7][8][9][10][11] These findings indicate that adverse prenatal or intrauterine environments might contribute to the development of high RE later in life. 12 Hypertensive disorder of pregnancy (HDP) is one of the most common complications during pregnancy, affecting 5% to 10% of pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of developmental origins of health and disease (DOHaD) theory has been widely accepted, which proposed that early life environmental factors have profound effects on vulnerability to disease in adulthood ( Haugen et al, 2015 ). Extensive range of clinical and epidemiological data suggested that gestational obesity and diabetes leave lasting impacts on the next generation, and so, the cycle of risk is perpetuated ( Godfrey et al, 2017 ; Chen et al, 2021b ; Du et al, 2021a ; Jiang et al, 2021 ; Lorenzon et al, 2021 ). Experimental research in animal models also showed that maternal high-fat diet (HF) during pregnancy and lactation predisposed offspring to metabolic disorders ( Zheng et al, 2014 ; Ribaroff et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We performed sibling comparison analyses to control for the influence of unmeasured familial and shared genetic characteristics [ 29 , 30 ]. A sub-sample of 6908 families including 17,315 siblings born to the same mother discordant for both DM and subsequent kidney diseases contributed to the effect estimate.…”
Section: Methodsmentioning
confidence: 99%